1998
DOI: 10.1021/np970382v
|View full text |Cite
|
Sign up to set email alerts
|

Antipoliovirus Structure−Activity Relationships of Some Aporphine Alkaloids

Abstract: A series of 18 aporphinoids have been tested in vitro against human poliovirus. The aporphines (+)-glaucine fumarate (1), (+)-N-methyllaurotetanine (4), (+)-isoboldine (7), and (-)-nuciferine, HCl (10) were found to be active with selectivity indices > 14. The nature of the 1, 2-substituents of the isoquinoline moiety appeared to be critical for antipoliovirus activity. An SAR study demonstrated the importance of a methoxyl group at C-2 on the tetrahydroisoquinoline ring for the induction of antipoliovirus act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 20 publications
1
38
0
3
Order By: Relevance
“…The biological activities and efficacy of these compounds depend on the structures of substituted groups and their position on the skeleton. The results of structure-activity relationship (SAR) studies on their adrenoceptor antagonist (Madrero et al, 1996;Martinez et al, 1999;Indra et al, 2002), cytotoxic (Likhitwitayawuid et al, 1993), antioxidative (Martinez et al, 1992;Cassels et al, 1995), antiplatelet aggregation (Chen et al, 1996(Chen et al, , 2000, immunosuppressant (Philipov et al, 1998) and antivirus activities (Boustie et al, 1998;Zhang et al, 2002) have been reported previously. Although a broad spectrum of bioactivities and SAR of the aporphine and benzylisoquinoline alkaloids have been reported, their antinociceptive effects have been rarely investigated.…”
Section: Introductionmentioning
confidence: 80%
“…The biological activities and efficacy of these compounds depend on the structures of substituted groups and their position on the skeleton. The results of structure-activity relationship (SAR) studies on their adrenoceptor antagonist (Madrero et al, 1996;Martinez et al, 1999;Indra et al, 2002), cytotoxic (Likhitwitayawuid et al, 1993), antioxidative (Martinez et al, 1992;Cassels et al, 1995), antiplatelet aggregation (Chen et al, 1996(Chen et al, , 2000, immunosuppressant (Philipov et al, 1998) and antivirus activities (Boustie et al, 1998;Zhang et al, 2002) have been reported previously. Although a broad spectrum of bioactivities and SAR of the aporphine and benzylisoquinoline alkaloids have been reported, their antinociceptive effects have been rarely investigated.…”
Section: Introductionmentioning
confidence: 80%
“…For antiviral activity of aporphine alkaloids, they were shown to interfere with the viral replicative cycle. Although DNA synthesis was reduced, their exact target remains to be elucidated (Boustie et al, 1998).…”
Section: Antimicrobial Activitiesmentioning
confidence: 99%
“…These free radicals may be to bind to macromolecular in liver cells covalently, and also attack saturated lipids, which can induce lipid peroxidation and lead to hepatocellular membrane damage (Koch et al, 1974). antilipase (Zhu et al, 2007) and antipoliovirus (Boustie et al, 1998).…”
Section: Introductionmentioning
confidence: 99%